Conference Review: Summa Summarum - Experimental Archaeology in the Balkans - Ivan Semyan; Spyros Bakas (EXARC Journal)
From May 30 to June 1, the 42nd conference of the Serbian Archeological Society was held in Negotin (Serbia). The session "Summa summarum - experimental archaeology in the Balkans" was co-organised with EXARC. About 130 experts from Germany, the USA, Poland, Greece, Latvia, Romania, Bulgaria, Bosnia, Slovenia, Croatia, Serbia, Russia and other countries took part in the event, and of these, several EXARC members presented their research: Vesna Vučković (RS), Milica Tapavički-Ilić (RS), Artūrs Tomsons (LV), Ivan Semyan (RU), Spyros Bakas (GR), Rene Masaryk (SI), Andreja Kudelić (HR), Tena Karavidović (HR) and Ina Miloglav (HR).